Effectiveness of Teacher Learning Devices on Concept Attainment Model Learning: Efektivitas Perangkat Pembelajaran Guru pada Pembelajaran Concept Attainment Model - Iwan Pranoto; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effectiveness of the learning tools used by teachers in learning the Concept Attainment Model in Class V SDI Raudlatul Jannah. This research is a descriptive qualitative research. The subjects of this study were the principal, class teacher, and students of V B SDI Raudlatul Jannah. Data collection techniques used are observation, interviews, and documentation. Data analysis using data reduction, data presentation and drawing conclusions. The results of the research show that the class V B teachers have carried out science learning on water cycle materials using CAM (Concept Attainment Model) oriented learning tools. The benefits of implementing learning with the Concept Attainment Model are that students play an active role in learning so that they can obtain information based on their experiences. Assessment techniques used by teachers are written tests, group work and assignments. Highlights: The effectiveness of Concept Attainment Model: This study aims to determine the effectiveness of the Concept Attainment Model in teaching science, specifically the water cycle, to fifth-grade students. Learning tools and techniques: The research highlights the use of learning tools, such as observation, interviews, and documentation, along with assessment techniques like written tests, group work, and assignments. Active role of students: The Concept Attainment Model promotes active learning, allowing students to actively engage in the learning process and acquire knowledge based on their experiences. Keywords: Concept Attainment Model, Learning Tools, SDI Raudlatul Jannah, Active Learning, Assessment Techniques